Extraction of high‐quality, high‐molecular‐weight DNA depends heavily on cell homogenization methods in green microalgae. (10th March 2020) - Stark, Jordan R.; Cardon, Zoe G.; Peredo, Elena L.
Abstract : Premise: New sequencing technologies have facilitated genomic studies in green microalgae; however, extracting high‐quality DNA is often a bottleneck for long‐read sequencing. Methods and Results: Here, we present a low‐cost, highly transferrable method for the extraction of high‐molecular‐weight (HMW), high‐purity DNA from microalgae. We first determined the effect of sample preparation on DNA quality using three homogenization methods: manual grinding using a mini‐pestle, automatic grinding using a vortex adapter, and grinding in liquid nitrogen. We demonstrated the versatility of grinding in liquid nitrogen followed by a modified cetyltrimethylammonium bromide (CTAB) extraction across a suite of aquatic‐ and desert‐evolved algal taxa. Finally, we tested the protocol's robustness by doubling the input material to increase yield, producing per sample up to 20 μg of high‐purity DNA longer than 21.2 kbp. Conclusions: All homogenization methods produced DNA within acceptable parameters for purity, but only liquid nitrogen grinding resulted in HMW DNA. The optimization of cell lysis while minimizing DNA shearing is therefore crucial for the isolation of DNA for long‐read genomic sequencing because template DNA length strongly affects read output and length.